Role of Whatsapp as a Teaching Aid to Enhance Learning Capabilities of Management Students - Kushwaha, Pooja S; Jhawar, Nidhi (Ushus Journal of Business Management, 2018)
The liberalising of Business Education in 1990 by the Indian Government has resulted in a large number of management schools offering management courses at graduate and post graduate levels. In the last five years, the number of B-school seats has grown three times. Excluding the few top B-schools like IIMs, most of the B-schools in the country are churning “unemployable” graduates. The paper uses convenience sampling to collect data from students and faculty members of different B-schools in order to find out their usage of digital technologies like Whatsapp for teaching and learning. It also explains the use of digital technology in curriculum designing. This further helps them in placing students in good profiles and better packages as they are able to share more practical real time insights with them.